The Influence of Salaries, Production Costs and Tax Costs on Transfer Pricing in Companies Registered at Bureau Van Dijk-Osiris In 2022 - Hutajulu, Dual Saper; Khomsiyah, Khomsiyah (Jurnal Indonesia Sosial Sains, 2023)
This study aims to determine the influence of Salary Expenses, Production Costs and Tax Expenses partially and simultaneously on Transfer Pricing, while the object of this study is a multinational company (Tbk) which is listed on the Van Dijk-Osiris Bureau 2022. Salary has a positive relationship to Transfer Pricing, so Salary Expense has no effect on Transfer Pricing which illustrates that when Salary Expense increases then Transfer Pricing practice decreases. This study aims to determine the influence of Salary Expenses, Production Costs and Tax Expenses partially and simultaneously on Transfer Pricing, while the object of this study is a multinational company (Tbk) that is listed on the Van Dijk-Osiris Bureau 2022. Salary has a positive relationship to Transfer Pricing, so Salary Expense has no effect on Transfer Pricing which illustrates that when Salary Expense increases then Transfer Pricing practice decreases. Production Costs have a positive relationship to Transfer Pricing, but the value is relatively small below 0.5 so the results of the Hypothesis test show that the Production Costs variable has no effect on Transfer Pricing which illustrates that when Production Costs increase, Transfer Pricing practices decrease. Tax Fees have a negative relationship to Transfer Pricing while the results of the hypothesis test show a significance value greater than 0.05, that Tax Fees have no effect on Transfer Pricing which illustrates that when Tax Expenses increase then Transfer Pricing practices will be low.